The risks of being a philanthropist: A risk-ethical analysis of philanthropy - Georg von Schnurbein (University of Basel, Center for Philanthropy Studies (CEPS), 2014)
Philanthropic acts aim at a change in habits or situation in the life of others. The current debate on performance measurement and professionalization of the philanthropic sector leads - despite the altruistic tenor of the acts - to the question, which consequences the beneficence has and to what extent a philanthropist has to take them into account in advance. Based on risk-ethical decision approaches this paper discusses several risks for the philanthropist and others. Practical examples and theoretical considerations are used to elaborate specific risks of philanthropy. Afterwards three elementary parameters are presented that a philanthropist may use in order to reduce the probability of the aforementioned risks.
Keywords: 330